ANALISIS KELAYAKAN PENGEMBANGAN USAHA DEPOT MAGS WATER DI MAKASSAR - Arifuddin Rahman; Muhammad Hidayat; Fitriani Latief (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2020)
This MAGS Water Depot business is an effort to Refill Drinking Water. The purpose of this research was to analyze the feasibility of non-financial and financial aspects of MAGS Water Depot. Data analysis methods used are qualitative (legal aspects, social and economic aspects, market and marketing aspects, management aspects and human resources and environmental aspects). While the quantitative analysis tool used for the feasibility of financial aspects uses analysis (Present value, Net present Value, Profitability Index, Pay Back Period, Internal rate of Return, Avarage Rate of Return) to find out whether or not it is feasible. The results of the research showed that MAGS Water Depot business from non-financial aspects was feasible to conduct from the legal aspects, social and economic aspects, management aspects and human resources and environmental aspects. The results of the analysis of the financial 10 years ahead show that MAGS Water Depot through Present Value analysis was Rp. 1,581,771,274.-, Net Present Value was Rp. 756,271,274.-, Profitability Index was 37%, Pay back Period was obtained for 3 years 2 months, Internal Rate of Return was 32%, while Avarage Rate of Return was 31% for 10 years.